Vibration and Acoustic Response of Rectangular Sandwich Plate under Thermal Environment - Yuan Liu; Yueming Li (Shock and Vibration)
In this paper, we focus on the vibration and acoustic response of a rectangular sandwich plate which is subjected to a concentrated harmonic force under thermal environment. The critical buckling temperature is obtained to decide the thermal load. The natural frequencies and modes as well as dynamic responses are acquired by using the analytical formulations based on equivalent non-classical theory, in which the effects of shear deformation and rotational inertia are taken into account. The rise of thermal load decreases the natural frequencies and moves response peaks to the low-frequency range. The specific features of sandwich plates with different formations are discussed subsequently. As the thickness ratio of facing to core increases, the natural frequencies are enlarged, and the response peaks float to the high-frequency region. Raising the Young's modulus of the core can cause the similar trends. The accuracy of the theoretical method is verified by comparing its results with those computed by the FEM/BEM.